Kesesuaian Teori Perkembangan Kognitif Piaget Pada Peserta Didik Kelas I Dan II Dalam Memahami Hukum Kekekalan - Faridatul Wardi; Laila Hayati; Nani Kurniati; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine the suitability of cognitive development of class I and II students in understanding the law of conservation of numbers, conservation of material and long conservation with Jean Piaget's theory of cognitive development. This type of research is quantitative with a qualitative-descriptive approach. This study population was 52 students in grades I and II at Madrasah Ibtidaiyah Al-Mukhtariyah Foundation Al-Islamiyah Mamben Daya Academic Year 2020/2021 with a sampling technique using a purposive sampling technique. Based on this technique, 14 research samples were obtained, six samples from class I and eight samples from class II. The instrument used was a test in the form of a brief description of the law of conservation of numbers, conservation of matter and conservation of length. The non-test instrument is an interview combined with a simple experiment. Interviews and simple experiments in this study use coins to the conservation of numbers, water and glass for the conservation of matter, and finally the rope for the conservation of length. Based on the results of the data analysis on the answers to the students' test questions, it is known that 50% of students already understand the law of conservation of numbers, the law of conservation of matter and the law of long conservation. Meanwhile, based on the results of interviews and simple experiments, it is known that 7 students have understood the law of conservation of numbers, conservation of matter and conservation of long, 2 students have understood the law of conservation of numbers and conservation of matter, 2 students have understood the law of conservation of numbers and conservation of length, 2 participants students understand the law of the conservation of numbers and 1 student who does not understand the three conservation laws. For further researchers, they can research the causes of students who have entered the concrete thinking stage and do not understand the law of eternity.